The mechanism of supplementary cementitious materials enhancing the water resistance of magnesium oxychloride cement (MOC): A comparison between pulverized fuel ash and incinerated sewage sludge ash. (May 2020) - He, Pingping; Poon, Chi Sun; Richardson, Ian G.; Tsang, Daniel C.W.
Abstract: Magnesium oxychloride cement (MOC) pastes incorporating supplementary cementitious materials (SCMs) including pulverized fuel ash (PFA) and incinerated sewage sludge ash (ISSA) were examined by scanning electron microscopy (SEM) and transmission electron microscopy (TEM) with energy dispersive X-ray spectrometry (EDX). The result showed that the mechanism of PFA and ISSA in improving the water resistance of MOC paste is similar, even though the molar ratios of the hydration product in the ISSA-incorporated paste and the PFA-incorporated paste were different. The active phases in PFA or ISSA could react with MgO and produce an amorphous phase (amorphous magnesium aluminosilicate gel), which was interspersed with Phase 5 and changed the morphology of Phase 5 to fibroid or lath-like phases. These fibroid or lath-like phases interlocked with each other and also connected with the amorphous phase in the matrix to form a stable compact structure. Therefore, the water resistance of MOC was improved. The ISSA-blended MOC paste had higher water resistance compared to the PFA-blended MOC, which may be due to the different chemical composition of amorphous phase and the dissolved phosphorus from ISSA.